Non-catalytic functions of Pyk2 and Fyn regulate late stage adhesion in human T cells. - Nicole M Chapman; Ashley N Yoder; Jon C D Houtman (PLoS ONE, 2012)
T cell activation drives the protective immune response against pathogens, but is also critical for the development of pathological diseases in humans. Cytoskeletal changes are required for downstream functions in T cells, including proliferation, cytokine production, migration, spreading, and adhesion. Therefore, investigating the molecular mechanism of cytoskeletal changes is crucial for understanding the induction of T cell-driven immune responses and for developing therapies to treat immune disorders related to aberrant T cell activation. In this study, we used a plate-bound adhesion assay that incorporated near-infrared imaging technology to address how TCR signaling drives human T cell adhesion. Interestingly, we observed that T cells have weak adhesion early after TCR activation and that binding to the plate was significantly enhanced 30-60 minutes after receptor activation. This late stage of adhesion was mediated by actin polymerization but was surprisingly not dependent upon Src family kinase activity. By contrast, the non-catalytic functions of the kinases Fyn and Pyk2 were required for late stage human T cell adhesion. These data reveal a novel TCR-induced signaling pathway that controls cellular adhesion independent of the canonical TCR signaling cascade driven by tyrosine kinase activity.